2020
DOI: 10.21203/rs.3.rs-59692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testicular Cancer Awareness among Men Residing in the Maltese Islands

Abstract: BackgroundTesticular cancer (TC) accounts for around one percent of all cancers in men. Early detection is of utmost importance for recovery and survivorship. Testicular self-examination (TSE) has been shown to be effective in preventing late-stage TC diagnosis. However, there is a lack of knowledge and awareness of both TC and TSE in men. Increasing such awareness may contribute towards earlier TC detection and positive outcomes. This study aims to assess the level of knowledge of a representative sample of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The current study illustrated that there was a highly statistically significant difference between male students' total practice and their source of information at p.value, moreover there was a statistically significant difference between male students' total practice and their age& Academic years at p value respectively, this outcome. Disagreement with Marmarà et al, (2020) who conducted study about "Testicular Cancer Awareness among Men Residing in the Maltese Islands" and revealed that the association between practice of TSE and prior history of TC in the family was significant and no significant associations between practice of TSE and age and level of education.…”
Section: Discussionmentioning
confidence: 94%
“…The current study illustrated that there was a highly statistically significant difference between male students' total practice and their source of information at p.value, moreover there was a statistically significant difference between male students' total practice and their age& Academic years at p value respectively, this outcome. Disagreement with Marmarà et al, (2020) who conducted study about "Testicular Cancer Awareness among Men Residing in the Maltese Islands" and revealed that the association between practice of TSE and prior history of TC in the family was significant and no significant associations between practice of TSE and age and level of education.…”
Section: Discussionmentioning
confidence: 94%